Three-dimensional computer reconstruction of large tissue volumes based on composing series of high-resolution confocal images by GlueMRC and LinkMRC software - Karen, Petr; Jirkovská, Marie; Tomori, Zoltán; Demjénová, Erna; Janácek, Jirí; Kubínová, Lucie (Microscopy research and technique, 2003)
Computer-based visualization of large tissue volumes with high resolution based on composing series of high-resolution confocal images is presented. GlueMRC and LinkMRC programs are introduced, implementing composition of overlapping series of optical sections captured by a confocal microscope, registration and subsequent composition of successive confocal stacks. Both programs are using an interactive approach in combination with automatic algorithms for image registration. Further, the method for obtaining surface renderings of microscopical structure under study is described. For this purpose, structure contours visible in the sections are interactively digitized using a Colon plug-in module running in Ellipse environment. Then the coordinates of the contours are processed by special modules in the graphic programming environment IRIS Explorer and the structure surface is rendered. The method is shown on the 3-D reconstruction of the capillary bed of human placental villi and chick embryonic gut and its vascular bed.
Keywords: Animals; Digestive System; počítačové zpracování obrazu; Imaging, Three-Dimensional; kapiláry; kuřecí embryo; Humans; konfokální mikroskopie; choriové klky; Image Processing, Computer-Assisted; Software; lidé; trávicí systém; Capillaries; zvířata; software; Chorionic Villi; zobrazování trojrozměrné; Chick Embryo; Microscopy, Confocal